Studi Kelayakan Lokasi Bisnis Dengan Pendekatan Lifestyle Generasi Z : Peluang Untuk Usaha Kuliner - Maharani Maharani; Nanda Darista; Ghina Raudatul Janna; Andi Syawalia Fitriani; Hasni (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This study aims to evaluate the feasibility of culinary business locations. By placing Generation Z lifestyle as the main variable. The method used is a descriptive qualitative approach through direct observation of Generation Z. the results of the study show that locations with easy access, comfortable environments, high visual appeal, and supporting facilities such as WiFi and power outlets are very suitable for Generation Z social and digital preferences. Visitors are seen actively documenting their activities and sharing them through social media, indicating the importance of easthetic value and digital existence in determining business locations. Therefore, a lifestyle-based approach has proven effective in analyzing location feasibility and can be an adaptive strategy in building a sustainable culinary business that is relevant to the dynamics of the current young generation market